2008
DOI: 10.1152/ajpregu.00112.2008
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of estrogen-mediated intestinal protection following trauma-hemorrhage: p38 MAPK-dependent upregulation of HO-1

Abstract: p38 MAPK has been reported to regulate the inflammatory response in various cell types via extracellular stimuli. p38 MAPK activation also results in the induction of heme oxygenase (HO)-1, which exerts potent anti-inflammatory effects. Although studies have shown that 17beta-estradiol (E(2)) prevented organ dysfunction following trauma-hemorrhage, it remains unknown whether p38 MAPK/HO-1 plays any role in E(2)-mediated attenuation of intestinal injury under those conditions. To study this, male rats underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…26 Thyroid hormones 27 and estrogen 28 increase DHCR24 expression in human fetal neuroepithelial cells and also enhance HO-1 expression in the rat kidney 29 and intestine. 30 However, high dietary intake of the trace metal selenium reduces DHCR24 expression in the rat prostate, 31 whereas bovine aortic endothelial cells cultured in selenium-deficient medium have increased expression of HO-1. elements in the gene promoter region that can be stimulated by a range of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…26 Thyroid hormones 27 and estrogen 28 increase DHCR24 expression in human fetal neuroepithelial cells and also enhance HO-1 expression in the rat kidney 29 and intestine. 30 However, high dietary intake of the trace metal selenium reduces DHCR24 expression in the rat prostate, 31 whereas bovine aortic endothelial cells cultured in selenium-deficient medium have increased expression of HO-1. elements in the gene promoter region that can be stimulated by a range of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that estradiol enhances phosphorylation of Akt through IRS/p85 of PI3K association in adipocytes [58] and cardiac muscle [59]. Enhanced Akt phosphorylation is associated with increased plasma membrane GLUT4 population but without increasing glucose uptake in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that T-H followed by resuscitation induces lipid peroxidation and protein nitrosylation (10), both of which subside after administration of the testosterone receptor antagonist, flutamide (10). T-H followed by resuscitation heightens the expression of heme oxygenase-1 (HO-1), a protective enzyme, and the administration of E2 further increases its expression (11). In addition, it has been shown that E2 facilitates accumulation of iron in iron storage (12), suggesting that E2 increases iron storage capacity in the tissues, which in turn may decrease the prooxidative capacity of the intracellular free-iron pool.…”
Section: Introductionmentioning
confidence: 99%